Effects of Benzodiazepines on Acinar and Myoepithelial Cells - Mattioli, Tatiana M. F.; Alanis, Luciana R. A.; Sapelli, Silvana da Silva; de Lima, Antonio A. S.; de Noronha, Lucia; Rosa, Edvaldo A. R.; Althobaiti, Yusuf S.; Almalki, Atiah H.; Sari, Youssef; Ignacio, Sergio A.; Johann, Aline C. B. R.; Gregio, Ana M. T. (Frontiers in Pharmacology, 2016)
Background: Benzodiazepines (BZDs), the most commonly prescribed psychotropic drugs with anxiolytic action, may cause hyposalivation. It has been previously shown that BZDs can cause hypertrophy and decrease the acini cell number. In this study, we investigated the effects of BZDs and pilocarpine on rat parotid glands, specifically on acinar, ductal, and myoepithelial cells. Methods: Ninety male Wistar rats were divided into nine groups. Control groups received a saline solution for 30 days (C30) and 60 days (C60), and pilocarpine (PILO) for 60 days. Experimental groups received lorazepam (L30) and midazolam (M30) for 30 days. Another group (LS60 or MS60) received lorazepam or midazolam for 30 days, respectively, and saline for additional 30 days. Finally, other groups (LP60 or MP60) received either lorazepam or midazolam for 30 days, respectively, and pilocarpine for additional 30 days. The expression of calponin in myoepithelial cells and the proliferating cell nuclear antigen (PCNA) in acinar and ductal cells were evaluated. Results: Animals treated with lorazepam showed an increase in the number of positive staining cells for calponin as compared to control animals (p<0.05). Midazolam administered with pilocarpine (MP60) induced an increase in the proliferation of acinar and ductal cells and a decrease in the positive staining cells for calponin as compared to midazolam administered with saline (MS60). Conclusion: We found that myoepithelial cells might be more sensitive to the effects of BZD than acinar and ductal cells in rat parotid glands.